The Effectiveness of the Problem Based Learning Approach on Critical Thinking Ability in Thematic Learning - Lestari, Indah Cahyani; Wardani, Naniek Sulistya (Thinking Skills and Creativity Journal, 2022)
Critical thinking is one of the competencies that must be possessed by students. Therefore, the process of implementing learning must be able to improve students' critical thinking skills. This study aims to analyze the difference in effectiveness between the problem-based learning approach and conventional learning on the critical thinking skills of thematic learning of fifth grade elementary school students. This type of research is a quasi-experimental study with a nonequivalent control group design model. The research subjects were 60 grade V elementary school students. Data collection techniques using tests and observations. The assessment instruments used are test items and observation sheets equipped with an assessment rubric. The data analysis technique used was the T test. The results showed that the significance value (2-tailed) was 0.000 (less than 0.05), meaning that Ha was accepted and H0 was rejected. The average problem based learning and conventional learning on the critical thinking skills of thematic learning from the results of the T test is 74,333. So, it can be concluded that there is a difference in effectiveness between the problem-based learning approach and conventional learning on the critical thinking skills of thematic learning of fifth grade elementary school students.